Multi-criteria Decision Support for Strategic Program Prioritization at Defence Research and Development Canada - Ismaili, Hami (Université d'Ottawa / University of Ottawa, 2013)
The objective of this thesis research is to model the multiple program objectives used by Defence Research and Development Canada (DRDC) for the annual management and allocation of their broad range of Science and Technology (S&T) projects in order to best achieve the strategic goals of the agency and the government. This M.Sc. thesis presents methodologies, techniques and applications in Linear Programming (LP) and Multi-Criteria Decision Making (MCDM) for decision support in program prioritization and project selection of the DRDC S&T projects. The results of this research produce a model that supports decision makers effectively in the assignment of limited human and financial resources to competing S&T projects based on the evaluation of projects that merit funding and the multiple criteria established by the organization. While there is a well-defined set of criteria for the annual program formulation process, the selection procedure is currently based on simple scoring processes and expert judgement; it lacks a well-defined and structured analysis. The application of an MCDM framework is proposed to take advantage of the well-structured problem and improve annual renewal and ongoing monitoring or project performance measures. The results of the analysis provide a traceable and rigorous MCDM framework to evaluate the performance of DRDC S&T projects for enhanced resource allocation.
Keywords: MCDM; AHP; Prioritization